A homozygous CaSR mutation causing a FHH phenotype completely masked by vitamin D deficiency presenting as rickets - Szczawinska, Dorothea; Schnabel, Dirk; Letz, Saskia; Schöfl, Christof (Journal of Clinical Endocrinology and Metabolism, 2014)
Heterozygous inactivating calcium-sensing receptor (CaSR) mutations lead to familial hypocalciuric hypercalcemia (FHH), whereas homozygous mutations usually cause neonatal severe hyperparathyroidism.The objective of the study was to investigate the pathophysiological mechanisms of a homozygous inactivating CaSR mutation identified in a 16-year-old female.Clinical, biochemical, and genetic analyses of the index patient and her family were performed. Functional capacity of CaSRQ459R and CaSR mutants causing FHH (Q27R, P39A, S417C) or neonatal severe hyperparathyroidism (W718X) was assessed. Activation of the cytosolic calcium pathway and inhibition of PTH-induced cAMP signaling were measured.A 16-year-old girl presented with adolescent rickets, vitamin D deficiency, and secondary hyperparathyroidism. Vitamin D treatment unmasked features resembling FHH, and genetic testing revealed a homozygous CaSRQ459R mutation. Two apparently healthy siblings were homozygous for CaSRQ459R and had asymptomatic hypercalcemia and hypocalciuria. The CaSRQ459R mutation leads to mild functional inactivation in vitro, which explains the FHH-like phenotype in homozygous family members and the grossly exaggerated PTH response to vitamin D deficiency in the index case. The patient's parents and two other siblings were heterozygous, had normal serum calcium and PTH, but had marked hypocalciuria, which appeared to be associated with impaired in vitro activation of the calcium signaling pathway by CaSRQ459R. The Q459R mutation responded well to calcimimetic treatment in vitro.CaSR mutations causing mild functional impairment can lead to FHH, even in homozygous patients. The skeletal deformities in the index case were mainly due to severe vitamin D deficiency, and the CaSR mutation did not appear to have played a major independent role in the skeletal phenotype.
EVALuna2:1905

Amino Alcohol- (NPS-2143) and Quinazolinone-Derived Calcilytics (ATF936 and AXT914) Differentially Mitigate Excessive Signalling of Calcium-Sensing Receptor Mutants Causing Bartter Syndrome Type 5 and Autosomal Dominant Hypocalcemia - Letz, Saskia; Haag, Christine; Schulze, Egbert; Frank-Raue, Karin; Raue, Friedhelm; Hofner, Benjamin; Mayr, Bernhard; Schöfl, Christof (PLoS ONE, 2014)
Activating calcium sensing receptor (CaSR) mutations cause autosomal dominant hypocalcemia (ADH) characterized by low serum calcium, inappropriately low PTH and relative hypercalciuria. Four activating CaSR mutations cause additional renal wasting of sodium, chloride and other salts, a condition called Bartter syndrome (BS) type 5. Until today there is no specific medical treatment for BS type 5 and ADH. We investigated the effects of different allosteric CaSR antagonists (calcilytics) on activating CaSR mutants.All 4 known mutations causing BS type 5 and five ADH mutations were expressed in HEK 293T cells and receptor signalling was studied by measurement of intracellular free calcium in response to extracellular calcium ([Ca2+]o). To investigate the effect of calcilytics, cells were stimulated with 3 mM [Ca2+]o in the presence or absence of NPS-2143, ATF936 or AXT914.All BS type 5 and ADH mutants showed enhanced signalling activity to [Ca2+]o with left shifted dose response curves. In contrast to the amino alcohol NPS-2143, which was only partially effective, the quinazolinone calcilytics ATF936 and AXT914 significantly mitigated excessive cytosolic calcium signalling of all BS type 5 and ADH mutants studied. When these mutants were co-expressed with wild-type CaSR to approximate heterozygosity in patients, ATF936 and AXT914 were also effective on all mutants.The calcilytics ATF936 and AXT914 are capable of attenuating enhanced cytosolic calcium signalling activity of CaSR mutations causing BS type 5 and ADH. Quinazolinone calcilytics might therefore offer a novel treatment option for patients with activating CaSR mutations.
EVALuna2:1857

Heterozygous inactivating CaSR mutations causing neonatal hyperparathyroidism: function, inheritance and phenotype - Glaudo, Markus; Letz, Saskia; Quinkler, Marcus; Bogner, Ulrich; Elbelt, Ulf; Strasburger, Christian J.; Schnabel, Dirk; Lankes, Erwin; Scheel, Sandra; Feldkamp, Joachim; Haag, Christine; Schulze, Egbert; et al. (European Journal of Endocrinology, 2016)
Homozygous inactivating mutations of the calcium-sensing receptor (CaSR) lead to neonatal severe hyperparathyroidism (NSHPT), whereas heterozygous inactivating mutations result in familial hypocalciuric hypercalcemia (FHH). It is unknown why in some cases heterozygous CaSR mutations cause neonatal hyperparathyroidism (NHPT) clinically similar to NSHPT but with only moderately elevated serum calcium.A literature survey was conducted to identify patients with heterozygous CaSR mutations and NHPT. The common NHPT CaSR mutants R185Q and R227L were compared with 15 mutants causing only FHH in the heterozygous state. We studied in vitro calcium signaling including the functional consequences of co-expression of mutant and wild-type (wt) CaSR, patients' phenotype, age of disease manifestation and mode of inheritance.All inactivating CaSR mutants impaired calcium signaling of wt-CaSR regardless of the patients' clinical phenotype. The absolute intracellular calcium signaling response to physiologic extracellular calcium concentrations in vitro showed a high correlation with patients' serum calcium concentrations in vivo, which is similar in NHPT and FHH patients with the same genotype. Pedigrees of FHH families revealed that paternal inheritance per se does not necessarily lead to NHPT but may only cause FHH.There is a significant correlation between in vitro functional impairment of the CaSR at physiologic calcium concentrations and the severity of alterations in calcium homeostasis in patients. Whether a particular genotype leads to NHPT or FHH appears to depend on additional predisposing genetic or environmental factors. An individual therapeutic approach appears to be warranted for NHPT patients.
EVALuna2:2211